The cure for what ales you - Alexander, Ellie (Alexander, Ellie. Sloan Krause mysteries., 2022)
"Amateur sleuth and brewer Sloan Krause contends with her past -- and a murder related to it -- in The Cure for What Ales You, another delightful mystery from cozy writer Ellie Alexander. After a long cold winter, spring is beginning to bloom in the alpine village of Leavenworth, Washington, where craft brewer Sloan Krause and her partner in crime Garrett Strong are putting the finishing touches on their bright and refreshing Lemon Kiss ale. They'll be debuting their new line at the Maifest celebration, which will bring visitors from near and far to dance around the Maipole and shop at the outdoor flower markets. Despite the festive spirit in the air, Sloan is brewing over her past. She's spent months following leads that have turned into dead ends. But when she spots a woman who strongly resembles Marianne -- a long lost contact who may be her only connection to piecing together her story -- she hopes that things might be taking a turn in her favor. That hope is quickly smashed when Marianne is involved in the murder of a local housekeeper. To make matters worse, Marianne issues a dire warning that Sloan and her entire family are in danger. If Sloan can't figure out who the killer is and what happened in her past, she won't find any hoppy endings."--